2021
DOI: 10.3390/ma14040869
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Steel Slag Filler and Its Effect on Aging Resistance of Asphalt Mastic with Various Aging Methods

Abstract: Steel slag is the by-product of the steelmaking industry, the negative influences of which prompt more investigation into the recycling methods of steel slag. The purpose of this study is to characterize steel slag filler and study its feasibility of replacing limestone filler in asphalt concrete by evaluating the resistance of asphalt mastic under various aging methods. Firstly, steel slag filler, limestone filler, virgin asphalt, steel slag filler asphalt mastic and limestone filler asphalt mastic were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Steel slag filler is a high basicity filler, with strong adhesive bonding ability to asphaltbinder. Thus, as reported in the literature [30][31][32], steel slag utilization may valuably serve as an effective way to save the limited and diminishing natural resources. The chemical composition and mineral composition of steel slag are extremely complex, and the interaction between asphalt-binder and steel slag aggregate-filler depends on mechanical reinforcement and physicochemical interaction [33].…”
Section: Introductionmentioning
confidence: 83%
“…Steel slag filler is a high basicity filler, with strong adhesive bonding ability to asphaltbinder. Thus, as reported in the literature [30][31][32], steel slag utilization may valuably serve as an effective way to save the limited and diminishing natural resources. The chemical composition and mineral composition of steel slag are extremely complex, and the interaction between asphalt-binder and steel slag aggregate-filler depends on mechanical reinforcement and physicochemical interaction [33].…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, the volume ratio was used to mix the asphalt mortar, and the volume percentage of asphalt: steel-slag powder was 1:0.3. In addition, Wei et al [ 36 ] determined that the amount of asphalt and fillers was determined by the qualified asphalt concrete mix proportion, while the asphalt aggregate ratio was 4.9%. Therefore, the volume ratio of fillers to asphalt was determined as 0.3.…”
Section: Methodsmentioning
confidence: 99%
“…The excessive utilization of natural stones in the construction sector has led to a shortage of resources and environmental degradation, making it imperative to find economical and sustainable substitutes for conventional materials [ 27 , 28 ]. One area for substitution is the use of mineral powders in asphalt mixes, which can be completely or partially replaced by using waste materials such as waste tire rubber powder, slag, ceramic powder, calcareous sand, and volcanic ash [ 29 , 30 ]. Rochlani’s research showed that the porous structure and large specific surface area of ceramic powder are major factors that contribute to the higher stiffness, improved aging characteristics, stronger interaction between the asphalt and filler, and greater resistance to rutting in ceramic powder asphalt mastic [ 31 ].…”
Section: Introductionmentioning
confidence: 99%